Preparation, optimization and characterization of multiple unit microspheres containing kollidone SR - Marvin I Patel; Ravi R Patel; Jayvadan K Patel (Wolters Kluwer Medknow Publications, 2012)
The present investigation described the influence of viscosity and drug: Polymer ratio on Hydrochlorothiazide release. Floating microspheres loaded with hydrochlorothiazide were prepared by Emulsion solvent evaporation method. The prepared microspheres were evaluated by micromeritics properties, in vitro drug release, floating ability and drug entrapment efficiency.